DEKOMPOSISI KULIT KOPI OLEH BAKTERI SELULOLITIK YANG DIISOLASI DARI TIMBUNAN KULIT KOPI DI PERKEBUNAN KALIBENDO, JAWA TIMUR - Siska Nurfitriani; Eko Handayanto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2017)
Composting of coffee pulp takes a long time in PT.Perusahaan Perkebunan Kalibendo. To speed up the composting time from coffee pulp, a study that was aimed to isolate cellulolytic bacteria with the ability to decompose coffee pulp pulp was conducted at Soil Bology Laboratory, Faculty of Agriculture, Brawijaya University This study consisted of two phases, i.e. isolation and selection of cellulolytic bacteria originated from compost coffee pulp, and application of the selected bacteria onto the coffee pulp. Treatments tested in the secinda phase of this study were K0 (control or without the addition of isolates), K1 (with the addition of isolate SL 1), K2 (with the addition of isolate SL 2), K3 (with the addition of isolate SL 3) and K4 (with the addition of bacterial consortium). The treatments were arranged in a completely randomized design with three replicates. Parameters observed were decomposition rate, cellulose content, pH, C organic content, total N content, and physicals condition of the produced coffe pulp compost. Results of this study indicated that isolated bacteria obtained ware able to produce cellulase enzymes that could be seen from the presence of clear zone around bacterial colonies grown on Carboxymethyl Cellulose (CMC) agar medium. Three of eight isolated cellulolytic bacteria (SL1, SL2, and SL3) were capable of forming biggest clear zone on CMC medium with an average index of cellulolitic of 1.53. Bacterial isolates originated from coffee pulp compost were capable of decomposing coffee pulp. The bacteria consortium treatment (K4) was capable of decomposing coffee pulp faster than other treatments with the decomposition rate of 2.13 g/day